Review of Covid-19 vaccine clinical trials - A puzzle with missing pieces - Kwok, Hang Fai (Int J Biol Sci, 2021)
A year after the initial outbreak of Covid-19 pandemic, several Phase III clinical trials investigating vaccine safety and efficacy have been published. These vaccine candidates were developed by different research groups and pharmaceutical companies with various vaccine technologies including mRNA, recombinant protein, adenoviral vector and inactivated virus-based platforms. Despite numerous successful clinical trials, participants enrolled in these trials are limited by trial inclusion and exclusion criteria, geographic location and viral outbreak situation. Many questions still remain, especially for specific subgroups, including the elderly, females with pregnancy and breastfeeding status, and adolescents. At the same time, vaccine efficacy towards asymptomatic infection and specific viral variants are still largely unknown. This review will cover vaccine candidates with Phase III clinical trial data released and discuss the scientific data available so far for these vaccine candidates for different subgroups of people and different viral variants.